2016
DOI: 10.1021/acs.jpca.6b03187
|View full text |Cite
|
Sign up to set email alerts
|

On Dipole Moments and Hydrogen Bond Identification in Water Clusters

Abstract: It is demonstrated that the localized orbitals calculated for a water cluster have small delocalization tails along the hydrogen bonds, that are crucial in determining the resulting dipole moments of the system. (By cutting them, one gets much smaller dipole moments for the individual monomers-close to the values one obtains by using a Badertype analysis.) This means that the individual water monomers can be delimited only in a quite fuzzy manner, and the electronic charge density in a given point cannot be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
4
22
0
1
Order By: Relevance
“…Mayer have shown that in water molecules the dipole moment enhances with the cluster size [44]. In the present cause, we observed almost odd-even oscillation for larger size DMSO clusters, when the dipole moment is plotted as a function of cluster size (See Fig.…”
Section: Energetics' and Choice Of Functionalssupporting
confidence: 67%
See 1 more Smart Citation
“…Mayer have shown that in water molecules the dipole moment enhances with the cluster size [44]. In the present cause, we observed almost odd-even oscillation for larger size DMSO clusters, when the dipole moment is plotted as a function of cluster size (See Fig.…”
Section: Energetics' and Choice Of Functionalssupporting
confidence: 67%
“…Furthermore, the use of BSSE correction increases the BE values. Prior studies on the molecular aggregates have shown that the counterpoise correction provides error as the fragments within the complex is improved by the basic functions, while such extension is not possible in the calculation of the isolated fragments Venkataramanan Page 15 [44]. Recently, Grimme et al showed that incorporation of dispersion for geometrical optimization provides better results than performing BSSE correction [45].…”
Section: Energetics' and Choice Of Functionalsmentioning
confidence: 99%
“…It has been shown through detailed quantum calculations that the dipole moment and polarization of water increases with the degree of hydrogen bonding. 26,28,29,34,35 For instance, the dipole moment of a water monomer in the gas phase is 1.855 D, while calculations shows that the average dipole of individual water molecules is ~ 2.1 D in hydrogen bonded dimers and ~2.3 D in cyclic trimer clusters. 26 In this work we wish to employ insight gained from these detailed first principles calculations to estimate the coefficients in Eq.…”
Section: D: Application To Watermentioning
confidence: 99%
“…The results obtained using the proposed methodology agrees qualitatively better with the experimental IR, NMR, and CD spectra, compared with other methodologies. Despite of some interactions between solvent and solute were neglected due to the formulation of the method, is considered that the dipole moment of the solvents should have influence on the specific electric interactions between the solvents and the DHPT molecules (water = 1.84 Debye for an isolated water monomer and ~2.5 to 2.8 Debye in condensed phase, DMSO = 3.96 Debye).…”
Section: Resultsmentioning
confidence: 99%